2017
DOI: 10.1002/hep4.1052
|View full text |Cite
|
Sign up to set email alerts
|

Significant association between FOXP3 gene polymorphism and steroid‐resistant acute rejection in living donor liver transplantation

Abstract: Previous studies have found that preferential accumulation of regulatory T (Treg) cells in liver allografts during acute cellular rejection (ACR) is associated with less severe rejection, suggesting a role of Treg cells in preventing excessive progress of ACR. We investigated the impact of single nucleotide polymorphisms (SNPs) in the Forkhead box P3 (FOXP3) gene, a master regulator gene of Treg cells, on ACR severity in liver transplant (LT) recipients. In total, 102 living donor LT patients were enrolled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
2
10
1
Order By: Relevance
“…In contrast, the SNPs 2232365 and rs3761548 of the FOXP3 gene have been analyzed in different studies concerning graft rejection. In agreement with our results, Verma et al did not observe any association between SNP rs2232365 and acute cellular liver transplant rejection . But, this study reported an association between the genotypes −3279AA and −3279CA of the SNP rs3761548 and steroid‐resistant acute cellular rejection .…”
Section: Demographic and Clinical Characteristics Of Liver Transplantsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, the SNPs 2232365 and rs3761548 of the FOXP3 gene have been analyzed in different studies concerning graft rejection. In agreement with our results, Verma et al did not observe any association between SNP rs2232365 and acute cellular liver transplant rejection . But, this study reported an association between the genotypes −3279AA and −3279CA of the SNP rs3761548 and steroid‐resistant acute cellular rejection .…”
Section: Demographic and Clinical Characteristics Of Liver Transplantsupporting
confidence: 92%
“…In agreement with our results, Verma et al did not observe any association between SNP rs2232365 and acute cellular liver transplant rejection . But, this study reported an association between the genotypes −3279AA and −3279CA of the SNP rs3761548 and steroid‐resistant acute cellular rejection . Yet, in this study liver grafted patients were not subdivided according to the time point of occurrence of acute cellular rejection.…”
Section: Demographic and Clinical Characteristics Of Liver Transplantsupporting
confidence: 91%
“…As the SNP rs3761548 represents a polymorphism situated in the promoter region of FOXP3 gene, it could influence, directly or indirectly, the expression of FOXP3 protein in Treg cells. Indeed, the SNP rs3761548 is situated in the core GGGCGG sequence of the binding site for a transcription factor called specificity protein‐1 (Sp‐1) . The SNP rs3761548 was found to be capable of modulating the interaction of the Sp‐1 with the promoter of FOXP3 gene .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a reduced FOXP3 expression was observed in subjects with AA genotype compared with individuals with AC and CC genotypes at SNP rs3761548 . Moreover, the AA genotype was introduced as a risk factor for a number of autoimmune diseases, allergic rhinitis, and allograft rejection . Thereby, the presence of the AA genotype or A allele at SNP rs3761548 may lead to a defect of the Treg cell activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation